Topic Modelling Using VSM-LDA For Document Summarization - Luthfi Atikah; Novrindah Alvi Hasanah; Agus Zainal Arifin (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Summarization is a process to simplify the contents of a document by eliminating elements that are considered unimportant but do not reduce the core meaning the document wants to convey. However, as is known, a document will contain more than one topic. So it is necessary to identify the topic so that the summarization process is more effective. Latent Dirichlet Allocation (LDA) is a commonly used method of identifying topics. However, when running a program on a different dataset, LDA experiences